1988
DOI: 10.1530/jrf.0.0830517
|View full text |Cite
|
Sign up to set email alerts
|

Release of prostaglandin F-2  and the timing of events associated with luteolysis in ewes with oestrous cycles of different lengths

Abstract: Ewes (N = 32) were bled every 2 h from 5 days before expected oestrus until the end of oestrus. Plasma concentrations were determined for progesterone to monitor luteal activity and for the prostaglandin F-2 alpha (PGF-2 alpha) metabolites, 15-keto-13,14-dihydro-PGF-2 alpha and 11-ketotetranor-PGF to determine uterine synthesis and release of PGF-2 alpha. Most of the variation in cycle length was associated with the time of onset of luteolysis, the timing of events after luteolysis being constant and not relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 20 publications
1
35
0
2
Order By: Relevance
“…In all groups the average cycle length was close to the longest individual cycle length reported in other breeds (Zarco et al 1988). However, it should be taken into account that in the present study it was assumed that the onset of estrus (and thus the onset of the estrous cycle) occurred in all animals 48 h after sponge removal (Wildeus 2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In all groups the average cycle length was close to the longest individual cycle length reported in other breeds (Zarco et al 1988). However, it should be taken into account that in the present study it was assumed that the onset of estrus (and thus the onset of the estrous cycle) occurred in all animals 48 h after sponge removal (Wildeus 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Zarco et al (1988) found that the timing of events after the onset of luteolysis is remarkably constant in sheep, and not related to the duration of the estrous cycle, making alterations in the duration of proestrus an unlikely cause of differences in the estrous cycle length.…”
Section: Discussionmentioning
confidence: 89%
“…Embriões viáveis devem estar presentes no útero até o dia 13 do diestro para fornecer sinal luteotrópico (Pineda, 1989). Se não há embriões viáveis presentes, o corpo lúteo regride rapidamente sob a influência da PGF2a, e a ovelha inicia outro ciclo (Zarco et al, 1988). Este processo repete-se durante subseqüentes ciclos até o final da estação reprodutiva, se a ovelha não se tornar prenhe.…”
Section: Groups With Different Superscripts Within the Same Columms Aunclassified
“…Já no bovino, a (FARIN et al, 1990;ROBERTS, 1991;ROBERTS et al, 1991). Como resposta, o IFNT inibe a transcrição de receptores de estrógenos (ESR1; SPENCER & BAZER, 1996) e ocitocina (OXTR; SPENCER & BAZER, 1996;CHEN et al, 2006) no endométrio inibindo a luteólise (ZARCO et al, 1988a;ZARCO et al, 1988b). Na ovelha, esse momento corresponde à elongação do blastocisto que passa de uma forma esférica para filamentosa entre os dias 10 e 17 da gestação (SPENCER et al, 2004) Receptores de interferon tipo I e genes estimulados por interferons (ISGs) Os receptores de interferon tipo I (IFNAR1 e IFNAR2) são expressos em todos os tecidos corporais e têm como função principal mediar respostas antivirais.…”
Section: Receptores De Prostaglandinasunclassified